Elisitasi Kebutuhan Sistem Absensi InfoKHS Menggunakan User Persona - Kurniawan, Muhammad Zaki; Wijaya, Daffa Yan; Purnawan, Aditya (Universitas Islam Syekh Yusuf, 2022)
InfoKHS is a platform for students to access and manage information about learning outcomes that have been and will be taken. In addition, infoKHS also has an additional feature in the form of attendance to make it easier for students and lecturers to make independent attendance, especially if lectures are conducted online. In improving the user experience of infoKHS and developing software, system requirements will be identified using the User Persona method.A User Persona is a fictitious representation of a persona. These fictional characters represent users of the product or target audience. You can characterize the product by conducting an in-depth analysis of datasets on gender, work, motivation, and more. The purpose of this research is to identify information related to the characteristics and needs of software users in order to generate potential user data based on assumptions about relevant topics, which can then be analyzed and used as a reference for software implementation during project development. Combined with the evaluation function. This new feature can provide information about students' abilities based on the assessments that have been obtained. The information is in the form of recommendations for the ability of each student's area of ​​interest, based on the assessment of courses related to their respective fields of interest, then implemented using a use case diagram.